Gruta Nova da Columbeira, Gruta das Salemas and Gruta da Figueira Brava : stratigraphy, and chronology of the pleistocene deposits - Antunes, M. Telles (2015)
The evidence concerning the most recent Neanderthals in Portugal and maybe in the world, comes from there basic sites: Gruta das Salemas and Gruta da Figueira Brava. For Gruta Nova da Columbeira, two human occupation lewvels were 14C dated: c. 7, 26400 ± 750 BP and c. 8, 28900 ± 950 BP. The industries (denticulates, rich in levallois facies scrapers) are exclusively late Mousterian; this , as well as the fauna and a neanderthalian tooth make this cave one of the reference Mousterian sites in the Iberian Peninsula. Gruta das Salemas - at the bottom, sediment gliding suggests that most of the basal deposits (and bones for 14C dating) came from the outside during a certain time span. Atypical implements have tentatively been ascribed to the Middle Palaeolithic. Bed 8 vielded a human decidual molar and was dated 24820 ± 550 BP,this being apparently too for the Mousterian. The concerned dating may be somewhat later than the lowermost c. 8 deposits. The Gruta da Figueira Brava is especially important because of the wealth of data it provides. The site resulted from karst erosion that broadened vertical diaclases, and mainly from marine abrasion during Tryrrhenian III event. The surfexcavated a broad and deep shelter: The consequent lowering of the sea level (until about - 60 meters) forstered the development of a littoral plain with dunes that was flooded again in the Holocene. Diagenetic CaCo3 consolidated the external part of eolic sand with its fossil contents into a hard sandstone. That, in turn, converted the shelter into the extant cave. The upper part of C. 2 bed shows some evidence of human walking, excavating and (much later) the sticking of amphorae. A neanderthalian tooth was found in C. 2 along with mammal, bird and other faunal remnants. These objects include marine shells, coprolithes, human food garbage, bone and lithic late Mousterian implements, including denticulates (non-levallois facies owing to the scarcity of better raw material), and quartz pebbles brought in by man. Found in C. 3 were fired stones, ashes and charcoal, as well as what seems to be burnt animal fat and resin. These elements suggest the use of for lighting. Much organic matter was eliminated. The accumulation of iron oxides may be the result of the cumulative effect of exposure and denudative processes. The sea (a few kilometers away from its present position) provided large quantities of molluscs and crabs. C. 2 was 14C dated 30930 ± 700 BP,the value for intermediate fraction being 30050 ± 550 BP.The dating may appear somwhat older than the real age. Th/U dating is 30561 + 11759 - 10725 BP.The homogenous lithic implements seem to indicate that the late Mousterian occupation was short and discontinuous: when temporarily abandoned by man, the shelter may have been frequented by bats and other animals such as hyenas and panther.